Simulation of the interaction between plasma turbulence and neutrals in linear devices. (August 2017) - Leddy, J.; Dudson, B.; Willett, H.
Highlights: Interaction between plasma and neutrals is highly non-linear leading to net differences between averaged profiles and turbulent profiles on the source terms from ionisation, recombination, and charge exchange. The net effect of turbulence is to increase the magnitude of the interactions, leading to larger ionisation sources and recombination sinks than in the non-turbulent case. Ionisation occurs at the centre of the linear device, where density and temperature are highest. Recombination and charge exchange have lower mean-free-paths so the interaction is more localised to the edge of the eddies. Charge exchange works to cool the plasma at the centre of the device, and heat the plasma at the edge, indicating some form of cross-field heat transport. Abstract: The interaction between plasma and neutrals within a tokamak dominates the behaviour of the edge plasma, especially in the divertor region. This area is not quiescent, but has significant perturbations in the density and temperature due to turbulent fluctuations. Investigating the interaction between the neutrals and plasma is important for accurately simulating and understanding processes such as detachment in tokamaks. For simplicity, yet motivated by tokamak edge plasma, we simulate a linear plasma device and compare the sources and sinks due to ionisation, recombination, and charge exchange for cases with and without turbulence. Interestingly, the turbulence systematically strengthens the interaction, creating stronger sources and sinks for the plasma and neutrals. Not only does the strength of the interactions increase, but the location of these processes also changes. The recombination and charge exchange have relatively short mean free paths, so these processes occur on the scale of the eddy fluctuations, while the ionisation is mostly unaffected by the turbulence.